1995
DOI: 10.1074/jbc.270.31.18691
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Human 5-Hydroxytryptamine1A Receptor in Sf9 Cells

Abstract: The possibility that Spodoptera frugiperda (Sf9) cells can provide an intact cell setting for reconstitution of the human 5-hydroxytryptamine1A (5-HT1A) receptor with mammalian G protein subunits was explored. The 5-HT1A receptor was found to assume an uncoupled phenotype when expressed alone in Sf9 cells at relatively high levels (5-34 pmol of receptor/mg of membrane protein), i.e. agonist-binding to the receptor was characterized by a relatively high Kd and an insensitivity to GTP. Co-expression of the recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
100
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 60 publications
4
100
4
Order By: Relevance
“…Distinct, yet to be revealed, structural features within the G protein binding regions of receptor subtypes must also be taken into account in such a model. For example, a previous study showed that the 5HT 1A receptor interacts similarly with G proteins containing ␤ 1 ␥ 2 , ␤ 1 ␥ 3 , or ␤ 1 ␥ 5 dimers (8), whereas the present study revealed that the ␣ 2A -adrenergic receptor prefers G proteins containing the ␤ 1 ␥ 2 or ␤ 1 ␥ 3 dimer over that containing the ␤ 1 ␥ 5 dimer. Thus, the G protein binding pockets of the ␣ 2A -adrenergic receptor and the 5HT 1A may possess subtle structural differences that result in either more or less receptor to G␣␤␥ contact depending on the identity of the ␥ subunit.…”
Section: Influence Of ␤␥ Composition On Coupling To Other G Proteincocontrasting
confidence: 54%
See 3 more Smart Citations
“…Distinct, yet to be revealed, structural features within the G protein binding regions of receptor subtypes must also be taken into account in such a model. For example, a previous study showed that the 5HT 1A receptor interacts similarly with G proteins containing ␤ 1 ␥ 2 , ␤ 1 ␥ 3 , or ␤ 1 ␥ 5 dimers (8), whereas the present study revealed that the ␣ 2A -adrenergic receptor prefers G proteins containing the ␤ 1 ␥ 2 or ␤ 1 ␥ 3 dimer over that containing the ␤ 1 ␥ 5 dimer. Thus, the G protein binding pockets of the ␣ 2A -adrenergic receptor and the 5HT 1A may possess subtle structural differences that result in either more or less receptor to G␣␤␥ contact depending on the identity of the ␥ subunit.…”
Section: Influence Of ␤␥ Composition On Coupling To Other G Proteincocontrasting
confidence: 54%
“…To date, in vitro studies examining the contribution of a limited number of ␤␥ dimers to the specificity of receptor coupling have not yielded the same high degree of discrimination shown in the in vivo studies cited above (8,9). The present study extended this analysis to the ␣ 2A -adrenergic receptor and to ␤␥ dimers that represent the most extensive degree of structural diversity examined to date.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…We chose to investigate the relationship between NHE and ERK in CHO-K1 fibroblasts which were transfected with the human 5-HT "A receptor, a prototypical G i α -linked receptor [26,27]. The relatively selective nature of the coupling of this receptor to G proteins would reduce potential ambiguities that might result from a more complex pattern of G protein coupling.…”
Section: Introductionmentioning
confidence: 99%